Research on the resistance of modified bolted connection under progressive collapse scenario. Issue 11 (August 2021) - Rong, Xian; Xu, Xiuchen; Du, Yansheng
Beam-to-column connection configurations, such as welded, bolted, and mixed welded-bolted connections, play an important role in structural resistance and ductility under middle column-removal scenarios. This paper illustrates full-scale laboratory tests of two steel frame assemblies with different connection details under the progressive collapse scenario. One specimen adopts the modified conventional technique which has reinforced welded flange-bolted web connection (SC-WR), and the other specimen uses a slotted-hole connection based on the former (SC-WB). The failure modes, load transfer mechanism, and vertical resistance are analyzed in the test. Both connection configurations exhibit satisfactory load resistance and ductility supply. Specimen SC-WB shows the higher ultimate vertical capacity and greater chord rotation at later catenary stage due to a sufficient redistribution of the stress with the modified bolted shear tab. Moreover, finite element models (FEM) are developed and validated against the test data. FEM can accurately simulate the mechanical behaviors and the failure of specimens, which can provide an effective reference for the beam-to-column connection configurations in similar working conditions. Finally, a simplified mechanical model is exhibited in accordance with the experimental and numerical results to reveal the effect of the catenary mechanism. This result suggests that the duration of the catenary mechanism, rather than the magnitude of the axial force, plays an essential role in the resistance of vertical load.